TYPICALOGICAL FEATURES OF CHILDREN'S SPACES IN PUBLIC FAMILY VISIT INTERIORS - Малік, О. І.; Абизов, В. А.; Булгакова, Т. В. (Art and Design, 2023)
Purpose. This study aims to identify the main typological features of spaces for children's temporary stay in public interiors for family visits, as well as to clarify such concepts as "public institution for family visits" and "children's space in public institutions for family visits". Methodology. The study used the analysis of literary sources; structural and systemic and comparative analysis; physical examinations; synthesis of research results. Results. The conceptual apparatus of environment design has been developed by clarifying the concepts of "public institution for family visits" and "spaces for children in public institutions for family visits". It was determined that spaces for children in the interiors of public institutions for family visits can be divided according to certain characteristics. The classification of spaces for children in public institutions for family visits is proposed according to the nature of the architectural space, the degree of "isolation", age differentiation, and according to the types of activities – functional filling of the space. Such a typology will help in the formation of space for children in a public institution for family visits, taking into account the function of the institution; in the design of the necessary play equipment and furniture in accordance with the specifics of the children's space and opens directions for further research regarding its design in accordance with the typological characteristics. Scientific novelty. The conceptual apparatus of environment design has gained further development, typological features of children's spaces in public institutions for family visits have been determined for the first time. Practical significance of the obtained results lies in the possibility of their application for designers when designing the interior and equipment for children's spaces in public institutions for family visits.